2020
DOI: 10.2147/dmso.s250463
|View full text |Cite
|
Sign up to set email alerts
|

<p>Obstructive Sleep Apnea Exacerbates Glucose Dysmetabolism and Pancreatic β-Cell Dysfunction in Overweight and Obese Nondiabetic Young Adults</p>

Abstract: This study aimed to investigate the effects of obstructive sleep apnea (OSA) on the pancreatic β-cells dysfunction and their implications in the glucose dysmetabolism of overweight and obese nondiabetic young adults. Materials and Methods: The cross-sectional analysis included 422 subjects (261 males/ 161 females) with the mean age of 27.77 ± 7.51 years and average body mass index (BMI) of 34.84 ± 5.69 kg/m 2. All subjects underwent polysomnography (PSG), oral glucose toleranceinsulin releasing test (OGTT-IRT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The summary characteristics of all included studies in the present meta‐analysis are listed in Table 1 . Eight were cohort studies 6 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 14 were cross‐sectional studies 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 and three were case–control studies 3 , 43 , 44 . A meta‐analysis of each study design was carried out separately.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The summary characteristics of all included studies in the present meta‐analysis are listed in Table 1 . Eight were cohort studies 6 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 14 were cross‐sectional studies 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 and three were case–control studies 3 , 43 , 44 . A meta‐analysis of each study design was carried out separately.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding study classifications, most of the studies included both female and male participants, except for three studies that included only men 3 , 22 , 24 and one study that included only women 36 . Eight studies reported OSA and IFG risk 3 , 6 , 31 , 36 , 37 , 40 , 41 , 42 ; 10 reported OSA and IGT risk 3 , 6 , 31 , 32 , 35 , 36 , 37 , 40 , 41 , 43 ; five reported IFG and/or IGT risk 6 , 30 , 33 , 34 , 40 ; and 19 reported OSA and type 2 diabetes mellitus risk 6 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 33 , 34 , 35 , 37 , 38 , 39 , 42 , 44 . Eight studies reported an association of OSA with type 2 diabetes mellitus according to AHI severity 23 , 26 , 28 ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations